Političnokulturni vidiki ocenjevanja ustreznosti Slovenije za vstop v Evropsko unijo - Novak, Bogomir (Teorija in praksa, 2000)
The article deals with evaluation of political and cultural aptitude of Slovenia to become a full member State of the EU. The observation based on a comparative analysis is made from the point of Slovenian strategic position between political cultures of the Balkans and the Western European countries. Due to the fact that the Slovenian territory has been a part of four states in one century, the Slovenia has to prove great ability for adaptation to the new situation in international politics. In order to join the EU and NATO integrations, Slovenia should create and realise the political and cultural possibilities. From the Western standpoint, democratisation of the political culture of Slovenia is only at the beginning. Due to the fact that Slovenians are a small nation, they have an inferiority complex, although they are already overcoming it since the independence. There are some differences between Slovenian and Serbian political culture, considered from the following criteria: national identity and relation to other nationalities and ethnicities, xenophobia and xenophilia, myths and history, rationality and irrationality, diligence and military action, exclusivism and inclusivism, heterogeneity and homogeneity with hegemonism, autocratism and democratization.
Keywords: integracijski procesi; European Union; Evropska unija; članstvo; mednacionalni odnosi; Slovenia; Slovenija; politična kultura; Balkan; Balkans